Pelaksanaan Hukum Terkait Pembajakan Hak Cipta Film Di Masa Pandemi Melalui Media Internet Menurut UU No. 28 Tentang Hak Cipta - Matthew Husada; R. Rahaditya (Jurnal Hukum Adigama, 2022)
The film is part of the copyright when the film is published, it will appear with exclusive rights, which consist of moral rights and economic rights. These two things cannot be separated from copyright. Because both rights are a gift for the hard work of the creator. However, even though there is a copyright in a film that has been protected by the state, piracy still exists even though it has been banned. Even though it has decreased, during the Covid-19 pandemic, piracy has increased. This is due to the emergence of official streaming services that offer benefits and low prices. With more and more choices, it makes film piracy increases. many advantages offered and also the price. this becomes a boomerang because it is increasingly mushrooming. It seems impossible for someone with no purchasing power to rent all the streaming platforms. Therefore, many people prefer to pirate than have to pay more. Sanctions for piracy itself vary from criminal sanctions and fines to even closing websites that have been proven to violate copyright. The public's lack of knowledge about intellectual property and people's habits has been the reason for the rampant piracy of films during the pandemic. This study uses a statutory approach. then use primary and secondary legal materials